Analyzing female labor supply: evidence from a Dutch tax reform - Nicole Bosch; Bas van der Klaauw (Institute for the Study of Labor (IZA), 2009)
Among OECD countries, the Netherlands has average female labor force participation, but by far the highest rate of part-time work. This paper investigates the extent to which married women respond to financial incentives. We exploit the exogenous variation caused by a substantial Dutch tax reform in 2001. Our main conclusion is that the positive significant effect of tax reform on labor force participation dominates the negative insignificant effect on working hours. Our preferred explanation is that women respond more to changes in tax allowances than to changes in marginal tax rates.
urn:nbn:de:101:1-20090622232
Keywords: H24; J22; J38; 330; Uncompensated wage elasticity; labor force participation; working hours; endogeneity; Frauenerwerbstätigkeit; Arbeitsangebot; Arbeitszeit; Steuerreform; Steuerwirkung; Niederlande